Polymer Based Whispering Gallery Mode Humidity Sensor - Ann Britt Petermann; Thomas Hildebrandt; Uwe Morgner; Bernhard Wilhelm Roth; Merve Meinhardt-Wollweber (Sensors, 2018)
Whispering gallery mode (WGM) resonators are versatile high sensitivity sensors, but applications regularly suffer from elaborate and expensive manufacturing and read-out. We have realized a simple and inexpensive concept for an all-polymer WGM sensor. Here, we evaluate its performance for relative humidity measurements demonstrating a sensitivity of 47 pm/% RH. Our results show the sensor concepts’ promising potential for use in real-life applications and environments.